2022
DOI: 10.1080/21645515.2022.2050105
|View full text |Cite
|
Sign up to set email alerts
|

The COVID-19 vaccine concerns scale: Development and validation of a new measure

Abstract: Reasons for COVID-19 hesitancy are multi-faceted and tend to differ from those for general vaccine hesitancy. We developed the COVID-19 Vaccine Concerns Scale (CVCS), a self-report measure intended to better understand individuals’ concerns about COVID-19 vaccines. We validated the scale using data from a convenience sample of 2,281 emergency medical services providers, a group of professionals with high occupational COVID-19 risk. Measures included the CVCS items, an adapted Oxford COVID-19 vaccine hesitancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Hamilton and Hagger [ 20 ] developed the Vaccination Concerns in COVID-19 Scale (VaCCS), but instead of fear, this tool measures beliefs and concerns about COVID-19 vaccines on 35 items included in eight subscales (socio-political, health beliefs and outcomes, trait measures, intentions to receive the COVID-19 vaccine). Similarly, Gregory et al [ 21 ] developed a seven-point COVID-19 Vaccine Concern Scale (CVCS). However, still, this measure examines the cognitive aspects of the perceived reasons, attitudes, and beliefs associated with hesitancy rather than the symptoms of fear of vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Hamilton and Hagger [ 20 ] developed the Vaccination Concerns in COVID-19 Scale (VaCCS), but instead of fear, this tool measures beliefs and concerns about COVID-19 vaccines on 35 items included in eight subscales (socio-political, health beliefs and outcomes, trait measures, intentions to receive the COVID-19 vaccine). Similarly, Gregory et al [ 21 ] developed a seven-point COVID-19 Vaccine Concern Scale (CVCS). However, still, this measure examines the cognitive aspects of the perceived reasons, attitudes, and beliefs associated with hesitancy rather than the symptoms of fear of vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…The main emphasis was on the "barriers" construct, and questions exploring the "self-efficacy" construct were not included, since we did not predict that this issue would be the driving force that would retrain immunodeficient patients from vaccination, as they were not reported by previous studies in IEI patients [11,37,38]. Additionally, the input was gleaned from validated vaccine hesitancy evaluation instruments and explanatory models [43][44][45][46][47][48], as well as insights gained from a pilot interview. Interview questions were offered to participants in two languages, Latvian and Russian, to facilitate effective communication.…”
Section: Data Collectionmentioning
confidence: 99%
“…However, it is noteworthy that there is a notable lack of reliable tools available for measuring the impact of fear, which might explain the scarcity of studies in this area. However, previous studies have revealed the availability of some tools tailored to measure different aspects related to vaccination, such as worry [16,17], confidence [18], hesitancy [19], or reluctance [20,21], and other tools specifically aimed at assessing psychological barriers to vaccination [22].…”
Section: Introductionmentioning
confidence: 99%